2002
DOI: 10.1073/pnas.162488599
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, topographic differentiation, and positional memory in human fibroblasts

Abstract: A fundamental feature of the architecture and functional design of vertebrate animals is a stroma, composed of extracellular matrix and mesenchymal cells, which provides a structural scaffold and conduit for blood and lymphatic vessels, nerves, and leukocytes. Reciprocal interactions between mesenchymal and epithelial cells are known to play a critical role in orchestrating the development and morphogenesis of tissues and organs, but the roles played by specific stromal cells in controlling the design and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
848
5
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 999 publications
(911 citation statements)
references
References 36 publications
49
848
5
9
Order By: Relevance
“…In other words, does HOX code function as postal code? Chang et al 29 characterized HOX gene expression patterns in adult human fibroblasts derived from skin at different anatomical sites and found that the fibroblasts showed the site-specific HOX gene expression patterns, suggesting that the fibroblasts maintained key features of HOX gene expression patterns established during embryogenesis. We performed cluster analysis of the 15 melanoma specimens based on the similarity of HOX gene expressions; however, this analysis did not lead to the sorting in accordance with the body sites from which they derived.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, does HOX code function as postal code? Chang et al 29 characterized HOX gene expression patterns in adult human fibroblasts derived from skin at different anatomical sites and found that the fibroblasts showed the site-specific HOX gene expression patterns, suggesting that the fibroblasts maintained key features of HOX gene expression patterns established during embryogenesis. We performed cluster analysis of the 15 melanoma specimens based on the similarity of HOX gene expressions; however, this analysis did not lead to the sorting in accordance with the body sites from which they derived.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs can be harvested from numerous tissues and locations and may have similar surface markers and growth characteristics, however these MSCs display distinct differences [19]. Some studies, including our own published studies [20], suggest that BMMSCs and adipose-derived MSCs (ASCs) are more closely related than to MSCs derived from placental tissues [20,21].…”
Section: Msc Tissue Of Originmentioning
confidence: 99%
“…We saw little or no decrease in the expression of these genes in HeLa cells after the same stresses. About one-half of the genes with specific increases in expression after DTT and menadione treatment in fibroblasts are expressed at a higher level in serum-starved (nondividing) fibroblasts than in fibroblasts grown in the presence of serum (Chang et al, 2002), suggesting that the increased expression of these genes might simply reflect cell cycle arrest. Some of these genes, however, could play an active role in arresting the cell cycle; indeed, several of the genes in this cluster are suspected to regulate proliferation (p53, MAX interacting protein 1, p53-inducible nuclear protein 1, cellular repressor of E1A-stimulated genes, and RB-inhibiting gene 1).…”
Section: A Putative Response To Oxidative Stress and Er Stress In Fibmentioning
confidence: 99%